The craftsmanship footage in Yunnan ethnic minority documentaries contributes to the construction of regional culture - Li, Chenxiao; Yaakup, Hani Salwah; Syed Zainudin, Sharifah Sofiah; Hj Mohammad Razi, Siti Aishah (Redfame Publishing Inc., 2024)
This study aims to explore the successful experiences in the portrayal and dissemination of the handicraft culture within Yunnan ethnic minority documentaries. Through exquisite visual presentations and the stories of artisans, Yunnan ethnic minority documentaries have sparked vigorous discussions on social media, played a significant role, and positively impacted the lives of many artisans. The research employs focus group methodology as the primary measurement approach, gathering materials through interactive discussions among group members. The study's findings reveal the impact of imagery narratives on the dissemination of Yunnan ethnic minority culture, emphasizing the importance of visual representation in enhancing people's understanding of traditional artisans and preserving their heritage. An authentic presentation of intangible cultural heritage maximizes public attention towards Yunnan ethnic minority artisans. Through this research, we gain in-depth insights into the successful portrayal and dissemination of handicraft culture within Yunnan ethnic minority documentaries, offering references and insights for the further enhancement of handicraft culture dissemination and preservation.